SYTUACJA OFIAR PRZESTĘPSTWA ZGWAŁCENIA PO NOWELIZACJI KODEKSU KARNEGO Z DNIA 13 CZERWCA 2013 R. - Ferenz, Jerzy M. (Zeszyty Prawnicze, 2016)
The Situation of Rape Victims after the Amendment of 13 June 2013to the Polish Penal Code Summary The paper describes the situation of rape victims in Poland following the amendment of 13 June 2013 to the Polish Penal Code. Under the new provisions rape is an offence prosecutable in proceedings officially brought by the public prosecutor. Hitherto rape charges were brought by the victim or the victim’s legal guardian. This study concerns the issue of the substantive and procedural legal consequences for the victim who does not want to testify because of the particular situation in which he/ she has found himself, e.g. rape trauma syndrome or dependence on the offender.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" /><br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />